Applying Corrigan’s progressive model of self-stigma to people with depression - Göpfert, Nele Cornelia; Heydendorff, Steffen Conrad von; Dreßing, Harald; Bailer, Josef (PLOS ONE, 2019)
Background: The progressive model of self-stigma describes four stages of internalizing stereotypes of mental illness: stereotype awareness, personal agreement, self-concurrence, and harm to self (i.e., self-esteem). Successive stages are postulated to be the most highly related. Endorsement is presumed to decrease by stage. The model has been supported in most but not all elements in various studies. The procedural character has not yet been investigated in one integrative model. The aim of this study was to test the progressive model of self-stigma in three respects: I) successive stages have the strongest associations, II) endorsements decrease with each stage, and III) the procedural character can be represented by one serial mediation model. Methods: A cross-sectional computer-based survey was conducted in two samples of patients with depression; one online sample (NA = 550; only self-report) and one clinical face-to-face sample (NB = 180; screening by treatment staff). The inclusion criteria were, age of 18-70 years, sufficient cognitive abilities and German language skills. IBM SPSS statistics 24 was used for Cronbach’s alphas, descriptive statistics, Spearman correlations, and Mann-Whitney-U tests. The PROCESS procedure for SPSS Version 3.00 was used for mediation analyses. Results: The results support the progressive model of self-stigma in people with depression in most respects: Endorsements for stereotype awareness were higher than for personal agreement and self-concurrence, and no relevant difference was found between personal agreement and self-concurrence. Successive stages had the strongest associations, with the exception of the association between stereotype awareness and self-esteem, which was higher than the association between stereotype awareness and personal agreement and self-concurrence. The association between stereotype awareness and self-esteem was mediated via personal agreement and self-concurrence. Conclusion The progressive model of self-stigma offers a theoretical foundation for the process research of self-stigma. Longitudinal research may investigate predictive effects and whether different stages of self-stigma require specific consideration in their prediction, consequences, and potential interventions.